2017
DOI: 10.25115/ecp.v10i21.1038
|View full text |Cite
|
Sign up to set email alerts
|

Satisfacción laboral de trabajadores de actividades deportivas y recreativas en turismo activo

Abstract: RESUMEN:La satisfacción laboral es un estado emocional sobre la percepción subjetiva de las experiencias laborales de los trabajadores, que afecta directamente en la calidad del servicio prestado. Por ello, El objetivo del estudio analizar la satisfacción laboral de los trabajadores de turismo activo y sus condiciones de trabajo, y el efecto de estas en su satisfacción laboral en la comunidad autónoma de Andalucía. Para determinar los niveles de satisfacción laboral, se utilizó la herramienta de "Overall Job S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 4 publications
0
4
0
10
Order By: Relevance
“…For instance, the average age of sports technicians ranges between 20 and 29 years, whereas those who work in management and administration are between 31 and 40 years old (Fisekçioglu & Duman, 2010;INCUAL 2008). Furthermore, it can be asserted that most of the sample in the present study did not have academic or professional training related to physical activity and sports, like those professionals who work in active or sports tourism (Grimaldi-Puyana et al, 2017), or those presented by Barranco et al (2015) who work as sports managers, which is against regulatory obligations (Catalonia, 2008;La Rioja, 2015;Extremadura, 2015;& Andalusia, 2016). The data of the present study are similar to those found in Turkey, where the profession is not regulated, and only 30% of sports employees have some training related to sports (Fisekçioglu & Duman, 2010;Sekendiz, Koçak & Korkusuz, 2009).…”
Section: Diagram 1 Main Motivation Of Employees Discussionmentioning
confidence: 73%
“…For instance, the average age of sports technicians ranges between 20 and 29 years, whereas those who work in management and administration are between 31 and 40 years old (Fisekçioglu & Duman, 2010;INCUAL 2008). Furthermore, it can be asserted that most of the sample in the present study did not have academic or professional training related to physical activity and sports, like those professionals who work in active or sports tourism (Grimaldi-Puyana et al, 2017), or those presented by Barranco et al (2015) who work as sports managers, which is against regulatory obligations (Catalonia, 2008;La Rioja, 2015;Extremadura, 2015;& Andalusia, 2016). The data of the present study are similar to those found in Turkey, where the profession is not regulated, and only 30% of sports employees have some training related to sports (Fisekçioglu & Duman, 2010;Sekendiz, Koçak & Korkusuz, 2009).…”
Section: Diagram 1 Main Motivation Of Employees Discussionmentioning
confidence: 73%
“…This study analysed the job satisfaction of PASS graduates, concluding that, with respect to extrinsic satisfaction, all the groups were moderately satisfied, whereas in general satisfaction it was the professionals in management (M=76.46), followed by teachers (M=75.18) and performance trainers (M=73.30) who were moderately satisfied compared to those who work in health/fitness (M=69.03) and other scopes (M=67.29), who were "indifferent". In this sense, most of the workers surveyed showed positive values toward general satisfaction (Grimaldi-Puyana et al, 2018;Grimaldi-Puyana et al, 2017;Sánchez-Alcaraz et al, 2014 andSánchez-Alcaraz, 2012). However, no study was found in the sports science literature that divides the analysis of job satisfaction by scopes; thereby, the conclusions could not be compared to those of other authors.…”
Section: Discussionmentioning
confidence: 96%
“…Thereby, the concept of satisfaction has been a topic of great scientific interest since the 1960s, from which the number of studies published has increased in different areas (Anaya & Suárez, 2004;Martín, Campos-Izquierdo, Jiménez & Martínez, 2007). Likewise, among Spanish publications, it is worth highlighting recent studies about job satisfaction in workers and volunteers that work with disabled athletes (Grimaldi-Puyana, Sánchez-Oliver, & Alcaraz- Rodríguez, 2018), sports and recreational activities in active tourism (Grimaldi-Puyana, Sánchez-Oliver, Alcaraz- Rodríguez, & Pérez-Villalba, 2017), models that measure organizational culture and job satisfaction in fitness centres (Gálvez-Ruiz, Grimaldi-Puyana, Sánchez-Oliver, Fernández-Gavira, & García-Fernández, 2017), sports technicians in padel and swimming (Sánchez-Alcaraz, Gómez-Parra, & García, 2014), and beach lifeguards (Sánchez-Alcaraz, 2012). Furthermore, there are studies published in the MOISES GRIMALDI-PUYANA, MARTA PÉREZ-VILLALBA, AINARA BERNAL-GARCÍA, ANTONIO…”
Section: Introductionmentioning
confidence: 99%
“…En este caso, se observa que es muy alta para el indicador 1.20 (Existen desigualdades salariales entre hombres y mujeres que ejercen cargos iguales o equivalentes), indicando que, aunque la media es alta, no hay un consenso en considerar que los salarios son iguales, independientemente del género. Esto difiere de los resultados presentados de Grimaldi-Puyana et al, (2017) Las medias más altas que la medianas e corresponden con las de las variables 1.1,1.7, 1.9, 1.10, 1.12, 1.13, 1.16, 1.18, 1.23, lo que indica que las personas se muestran de acuerdo con dichas afirmaciones. Cuando se preguntó por las evaluaciones de las competencias (1.7) el resultado indicó que los hombres perciben que la ejecución de las tareas se evalúa de una manera neutra, lo opuesto a o que las mujeres sienten al respecto.…”
Section: Mercado Laboral Desde La Perspectiva De Géneroen El Sector Tunclassified